ANALISIS KRITIS MAKNA KONOTASI DALAM LIRIK LAGU GALA BUNGA MATAHARI KARYA SAL PRIADI - Maria Winata, Yuli; Zoni Sulaiman; Zainah Asmaniah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Song lyrics, as part of poetic literature, often contain connotative meanings that are not explicitly conveyed. This study aims to analyze the connotative meanings contained in the lyrics of Sal Priadi's song